2021
DOI: 10.1002/adom.202101350
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Sample Ratiometric Organic Films for Naked‐Eye High‐Temperature Multi‐Threshold Indication

Abstract: Threshold temperature sensors are crucial for recording the thermal histories of environments under different scenarios. However, most organic threshold thermometers are not suitable for high‐temperature indication due to significant thermo‐facilitated emission quenching. Here, a series of ratiometric luminescent high‐temperature threshold organic film indicators have been realized by synergetic effects of intramolecular local excited to charge transfer states and disaggregation from excimer to monomer. Varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…[ 13,21 ] Nevertheless, the reports on high‐temperature threshold sensing above 100 °C are rather scarce. [ 14,19,22–24 ] This is because organic chromophores generally encounter significant emission quenching at heating due to thermally induced nonradiative deactivation. [ 25 ] Therefore, development of organic film threshold thermometers for large area and flexible high‐temperature indication is still highly demanded.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 13,21 ] Nevertheless, the reports on high‐temperature threshold sensing above 100 °C are rather scarce. [ 14,19,22–24 ] This is because organic chromophores generally encounter significant emission quenching at heating due to thermally induced nonradiative deactivation. [ 25 ] Therefore, development of organic film threshold thermometers for large area and flexible high‐temperature indication is still highly demanded.…”
Section: Introductionmentioning
confidence: 99%
“…To realize fast and convenient high temperature threshold readout, a robust and highly‐visible temperature indication is usually required. This is generally dependent on high‐contrast luminescence ON/OFF switching, [ 14,26 ] ambient thermochromism, [ 27,28 ] or luminescent thermochromism [ 11,22,29 ] for naked‐eye detection in an ambient atmosphere. Thermochromic chromophores have aroused enormous attentions to fabricate functional temperature threshold sensors because they provide fast and convenient naked‐eye detection, especially those which allow two or more outputs of those mentioned naked‐eye signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have developed a series of high-temperature ratiometric thermosensors and threshold thermometers in both solution and solid films based on triarylphosphine oxides by employing thermally controlled competition between different emissive behaviors. [33,[46][47][48][49] In this work, we have developed a series of novel heat-resistant organic fluorophores based on pyrrole-substituted triarylphosphine oxides and demonstrated that these materials show prominent hot exciton characteristics for high-temperature sensing and heat-tolerant OLEDs. This work demonstrates that such materials show great promise for use in high-temperature flexible thermomapping and information display.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many fluorescent molecules have been developed for sensing temperature in recent years, these molecules are commonly used in the dispersed state (e.g., solutions or polymers) to facilitate the change of molecular conformation or aggregation responding to different temperatures. Thus, the sensing temperatures of these reports are relatively high, at least above the melting point of solutions or above the glass transition point of polymers (commonly higher than 200 K). In this point of view, it is an exceptional advantage that crystal 4 is capable of sensing very low temperature (77–155 K).…”
mentioning
confidence: 99%